Impact of a Medical Journal on Residents’ Research - Haque, Anwar Ul-; Naseem, Lubna (International Journal of Pathology, 2018)
Background: To launch and sustain a medical journal based on high quality research articles and use-ful interesting case reports etc is not an easy task especially in a non conducive scientific culture and environment. International Journal of Pathology overcame difficulties of getting good papers through several mechanisms including motivating postgraduate students toward research and writing. The chal-lenges turned into opportunities toward better training of postgraduate residents may be a very healthy and welcome outcome! Aims & Objective: To assess the impact of International Journal of Pathology Medical Journal on De-partment of Pathology Residents’ Research. Study Design: Retrospective Cross Sectional Descriptive Study Site: Department Of Pathology, Pakistan Institute Of Medical Sciences, Islamabad Material & Methods: All 15 issues of International Journal of Pathology were reviewed to assess the impact of the International Journal of Pathology on the various aspects of the department as reflected from the papers published in the International Journal of Pathology (IJP). Numbers of original research articles and case reports authored by the postgraduate residents as first or second authors are deter-mined and calculated as percentage of the total articles published in the journal. In addition editorials and papers related to the specific areas of interest of the editors cum faculty members were included. Inclusion Criteria: All original research articles from Pakistan Institute of Medical Sciences where the first and second authors were residents. All editorials and articles in specific areas of the editors cum faculty members as described above. Exclusion Criteria: Articles from outside Pakistan Institute of Medical Sciences, original articles and case reports where residents were not first or second authors. Results: 43 % of the original articles and 44% case reports published in International Journal of Pa-thology were authored by the postgraduate residents of the Department of Pathology, PIMS. There were significant number of editorials and articles on ethical issues, teaching strategies and curricula, infection control & waste management, Cytopathology, Dermatopathology, Transfusion Medicine, his-tory of medicine and new ideas in pathology Conclusion: International Journal of Pathology was successful in generating good number of high quality articles from Department’s Residents improving postgraduate training and patient care.